Activation of CaMKKβ/AMPKα pathway by 2‐AG in human platelets. Issue 1 (3rd August 2017) - Signorello, Maria Grazia; Leoncini, Giuliana
Abstract: The objective of this study was to determine whether AMPK is activated by 2‐arachidonoylglycerol (2‐AG) and participates to the cytoskeleton control in human platelets. We found that 2‐AG stimulates the AMPKα activation through a Ca 2+ /Calmodulin‐dependent pathway as the specific inhibition of the CaMKKβ by STO‐609 inhibits the AMPKα phosphorylation/activation. Moreover, the CaMKKβ/AMPKα pathway activated by 2‐AG is involved in the phosphorylation of cofilin, vasodilator stimulated phosphoprotein (VASP), and myosin light chain (MLCs). These proteins participate to actin cytoskeletal remodelling during aggregation. We found that the phosphorylation/activation inhibition of these proteins is associated with a significant reduction in actin polymerization, aggregation, ATP, and α‐granule secretion. Finally, AMPKα activation, Cofilin, VASP, and MLCs phosphorylation are significantly reduced by SR141716, the specific inhibitor of type 1 cannabinoid (CB1) receptor, suggesting that the CB1 receptor is involved in the 2‐AG effect. In conclusion, we have shown that the CaMKKβ/AMPKα pathway is activated by 2‐AG in human platelets and controls the phosphorylation of key proteins involved in actin polymerization and aggregation. Abstract : 2‐AG stimulates the AMPK activation through a Ca2+/Calmodulin‐dependent pathway as the specific inhibition of the CaMKK by STO‐609 produces the inhibition of AMPK phosphorylation/activation. CaMKK/AMPK pathway activated by 2‐AG is involved in the phosphorylation of cofilin, vasodilator stimulated phosphoprotein (VASP), and myosin light chain (MLCs) that participate to actin cytoskeletal remodelling during aggregation. CaMKK/AMPK pathway is activated by 2‐AG in human platelets and controls the phosphorylation of key proteins involved in actin polymerization, aggregation, ATP, and alfa‐granule secretion.